Can She Have It All? Pregnancy Narratives in Contemporary Category Romance - Annika Rosanowski (Journal of Popular Romance Studies, 2019)
Representations of pregnancy have shifted greatly over time and in Western cultures it currently revolves around pregnancy as a form of success: pregnant celebrities wear the latest trends and look fabulous, active mothers choose their preferred model of jogging strollers, and a whole array of films feature pregnant career women. Pregnancy is used as a vehicle to negotiate anxieties about reproductive technologies, so-called welfare queens, and the increasing number of single-parent households. This article focuses on category romance and the ways in which it reflects these discourses while allowing the articulation of some feminist values, such as women’s right to have a career as well as a family. Yet, examining pregnancy in the two Harlequin imprints “Presents” and “Romance,” reveals it to be women’s “biological destiny.” The heroine’s fulfillment, her happy end, is only made possible by having a baby and the necessity of a baby for fulfillment is not the same as being able to “have it all,” seeing that the baby now becomes mandatory for happiness. Furthermore, the fetus always has to come first—if one wants to avoid the label “bad” mother; category romance thereby employs pregnancy as a disciplinary tool that ultimately reinforces patriarchal ideology.